2020
DOI: 10.9734/ajaees/2020/v38i230309
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Social Networking Tools by Rural Youth in Transfer of Technology - An Overview

Abstract: The utilization of social media tools is an integral part of rural youth lives today. Over some time utilization of social media has been changed the attention of rural youth. The development of rural youths on social media has reached at a different level, without social media, every individual of rural youth cannot think about the direction of their respective growth and futures. The research studies on the utilization of social media conducted across the world by different authors and review extensively for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…From the study, it was also analyzed that social media should also be used for the health and medication sector. Radhakrishnan et al, (2020) in the research Usage of Social Networking Tools by Rural Youth in Transfer of Technology-An Overview explained that social media tools integration is highly seen in the lives of rural youth. It is observed that for future decisions also rural youth is dependent on social media.…”
Section: Reviewmentioning
confidence: 99%
“…From the study, it was also analyzed that social media should also be used for the health and medication sector. Radhakrishnan et al, (2020) in the research Usage of Social Networking Tools by Rural Youth in Transfer of Technology-An Overview explained that social media tools integration is highly seen in the lives of rural youth. It is observed that for future decisions also rural youth is dependent on social media.…”
Section: Reviewmentioning
confidence: 99%